Social Capital and Cost of Bank Loans During the Financial Crisis - Hmaittane, Abdelmajid; Mnasri, Mohamed; Bouslah, Kais; M’Zali, Bouchra (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This study examines the effect of the lender’s social capital on the link between the borrower’s social capital and the cost of bank loans. We exploit the last financial crisis as an exogenous shock to trust during which social capital becomes more valuable. Our findings suggest that when a lender’s social capital is high, borrowers with high social capital pay 46.22 basis points less on their bank loans than those with low social capital.